Association Between Serum Uric Acid and Nonalcoholic Fatty Liver Disease: A Case Control Study - Jibran Umar Ayub Khan, Humera Fayaz, Abdul Wahab, Syeda Faza Gul, Syed Haseeb Ullah Jan Bacha, Saman Babar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is one of the cardinal diseases of liver with wide spectrum of clinical features’ and its own complications in long run ranging from impaired glucose tolerance to frank liver cirrhosis Objective: To determine the relationship between serum uric acid level and NAFLD Materials and Methods: This case control study was conducted at MMC General Hospital Peshawar from January 2022 to June 2022. The total sample size is 100 . In this study we included 50 cases and 50 controls. Cases were patients who were diagnosed with fatty liver disease on ultrasound and controls were normal without having fatty liver disease. Data entry and analysis was done with SPSS version-25. Quantitative variables were presented with mean±SD and qualitative variables with frequency and percentage.Box plot was made to compare uric acid level among cases and controls. Uric acid level (Normal/Raised) was compared among cases and controls with Chi Square test with p value less than 0.05 as significant. Results: Among cases 35(70%) patients and among controls 20(40%) participants were had raised uric acid. Frequency of raised uric acid was significantly higher among cases as that of controls. i.e. 70% vs. 40%, p-value=0.003 Odds ratio of 3.5 shows that risk of raiseduric acid is 3.5 times higher for cases as that of controls. Conclusion: There is an association between NAFLD and high uric acid level indicating the need for regularly screening such patients. Keywords: NAFLD, Cirrhosis